Mixed economy and dried foods: Dental indicators reveal Heishuiguo Han Dynasty population's environmental adaptation to the semi‐arid region of northwestern China. (27th July 2022) - Xiong, Jianxue; Chen, Guoke; Yang, Yishi; Meng, Hailiang; Storozum, Michael; Allen, Edward; Wang, Hui; Wen, Shaoqing
Abstract: Situated in the middle Hexi corridor, a vital passage of the ancient Silk Road, the Heishuiguo site was a military town on the northwestern frontier of the Han Dynasty (202 BCE–220 CE). To understand the lifestyle of the Heishuiguo population, levels of dental caries and tooth wear were assessed. Archaeological findings and historical records revealed a mixed subsistence strategy dependent upon agricultural production and domesticated animals at Heishuiguo. This was also supported by evidence from stable isotope analysis. Teeth are an excellent material for the reconstruction of ancient diet, subsistence strategies, and social behavior. The rate of dental caries in the Heishuiguo population fell into the range of mixed economic population. Tooth wear analysis, however, shows a conflicting result. Anterior tooth wear is particularly severe at Heishuiguo, indicating subsistence practices similar to hunter‐gatherers and modern Xinjiang Kazakhs. As a major Han garrison, the majority of the Heishuiguo populace were either immigrants or the descendants of immigrants. Their diet, with rich nutritional value, portability, and adapted to long‐term preservation needs, suited environmental requirements at Heishuiguo. However, these foods generally required heavier use of cutting and tearing motions with the anterior teeth. Frequent occlusion (alignment) as a result of such actions resulted in severe tooth wear. Such tooth wear may be attributed to a preference for tough, dry foods, such as nang cake along the Heishuiguo population, as well abundant meat consumption. Such a dietary culture resulted from the hot and dry climate, complex geographical conditions, and abundant resources at Heishuiguo. The result was that a unique lifestyle and dietary culture gradually formed at Heishuiguo due to this creative adaptation to the local environment.